Research progress on the application of high-power laser cutting, welding, and drilling - Wang, Yu-Guo; Hou, Shu-Ping; Lv, Qing-Chen (Frontiers in Physics, 2025)
High-power laser technology has become an important tool in the field of modern machining due to its high energy density, non-contact processing characteristics and high-precision control ability to make it show significant advantages in cutting and welding. With the continuous development of laser technology, the application of high power laser (such as fiber laser, CO2 laser) in the industrial field is also expanding. This paper combs through the technical advantages, application research, challenges and future trends of high power lasers in cutting, welding and drilling. In recent years, the increase of laser power and the optimization of processing have promoted the wide application of high-power lasers in aerospace, automotive manufacturing and electronic devices. In this paper, we will discuss laser cutting, welding and drilling, and discuss their future development directions in light of recent research progress.